2020
DOI: 10.3390/f11040363
|View full text |Cite
|
Sign up to set email alerts
|

The C:N:P Stoichiometry of Planted and Natural Larix principis-rupprechtii Stands along Altitudinal Gradients on the Loess Plateau, China

Abstract: Carbon:nitrogen:phosphorus (C:N:P) stoichiometry plays a critical role in nutrient cycling, biodiversity, and ecosystem functionality. However, our understanding of the responses of C:N:P stoichiometry to elevation and forest management remains elusive. Here we sampled 18 Larix principis-rupprechtii sites along altitudinal gradients (1700-2300 m) on Guandishan Mountain in the Loess Plateau, China. We determined the leaf, litter, and soil C N P contents and C:N:P stoichiometric ratios, as well as nutrient resor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Among the observed variables, elevation was an essential environmental factor that correlated negatively to the stoichiometric ratio of plant and litter, and air temperature had an indirect positive effect on the stoichiometric ratio of plants (Table 2). This result corresponds with Bo et al [51], who observed that plant growth requires more nutrients (mainly N and P) to adapt to changes in the surrounding environment under cold climates, resulting in a smaller increase in C than N and P contents and a smaller increase in N than P contents. Soil pH was the main environmental factor that correlated negatively to the soil stoichiometry ratio (Table 2), which has been proved by previous studies on microbial composition affected by pH in an arable soil [52][53][54].…”
Section: Environmental Factors Affecting the Stoichiometric Ratio Of ...supporting
confidence: 91%
“…Among the observed variables, elevation was an essential environmental factor that correlated negatively to the stoichiometric ratio of plant and litter, and air temperature had an indirect positive effect on the stoichiometric ratio of plants (Table 2). This result corresponds with Bo et al [51], who observed that plant growth requires more nutrients (mainly N and P) to adapt to changes in the surrounding environment under cold climates, resulting in a smaller increase in C than N and P contents and a smaller increase in N than P contents. Soil pH was the main environmental factor that correlated negatively to the soil stoichiometry ratio (Table 2), which has been proved by previous studies on microbial composition affected by pH in an arable soil [52][53][54].…”
Section: Environmental Factors Affecting the Stoichiometric Ratio Of ...supporting
confidence: 91%
“…This may be because photosynthesis was inhibited when the temperature dropped with an increase in elevation, which in turn weakened their carbon assimilation ability (Öquist, 1983 ). However, some studies (e.g., Zhao et al, 2018 ; Bo et al, 2020 ; Waigwa et al, 2020 ) reported that [C] leaf tended to be greater at higher elevations to balance cell osmotic pressure and improve the frost resistance of plants (Zhao et al, 2018 ). These conflicting results suggest that the response of [C] leaf to elevation still requires further studies based on species and at the regional level.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships between leaf stoichiometry and environmental factors, including soil nutrients and geographical and climatic factors, were widely explored at various scales including regional and global scales (e.g., McGroddy et al, 2004 ; Reich and Oleksyn, 2004 ; Sardans et al, 2011 ; Du et al, 2017 ; Tian et al, 2018 ; Qin et al, 2021 ). Elevation is a crucial factor and can affect plant leaf stoichiometry by altering the combination of heat and water, soil properties, and vegetation community composition (Bo et al, 2020 ; Liu et al, 2021 ). However, there is little consensus on leaf stoichiometric characteristics as they change along an elevation gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al [ 30 ] have also concluded that there is a strong correlation between leaf stoichiometry and water use efficiency in plants. Meanwhile, leaf C:N:P stoichiometry is significantly affected by many factors, including climate [ 31 , 32 ], external nutrient availability [ 33 , 34 ], arbuscular mycorrhiza [ 16 , 17 ] and environmental conditions [ 35 , 36 ]. However, the relationship between senesced leaves’ stoichiometry and plant mycorrhizal association remains unknown.…”
Section: Introductionmentioning
confidence: 99%